Division of Short Gastric Vessels at Laparoscopic Nissen Fundoplication: A Prospective Double-Blind Randomized Trial With 5-Year Follow-Up - O’Boyle, Colm J. (2002)
OBJECTIVE: To determine whether division of the short gastric vessels at laparoscopic fundoplication confers long-term clinical benefit to patients. SUMMARY BACKGROUND DATA: Dividing the short gastric vessels during surgery for gastroesophageal reflux is controversial. This prospective randomized study was designed to determine whether there is a benefit in terms of patient outcome at a minimum of 5 years after primary surgery. METHODS: Between May 1994 and October 1995, 102 patients undergoing a laparoscopic Nissen fundoplication were randomized to have their short gastric vessels either divided or left intact. By September 2000, 99 (50 no division, 49 division) patients were available for follow-up, and they all underwent a detailed telephone interview by an independent and masked investigator. RESULTS: There were no significant differences between the groups at 5 years of follow-up in terms of the incidence of epigastric pain, regurgitation, odynophagia, early satiety, inability to belch, anorexia, nausea, vomiting, nocturnal coughing, and nocturnal wheezing. There was also no difference between the groups in the incidence of heartburn when determined by either yes/no questioning or a 0-to-10 visual analog scale. There was no difference between the groups in terms of the incidence and severity of dysphagia determined by yes/no questioning, 0-to-10 visual analog scales, or a composite dysphagia score. There was a significantly increased incidence of flatus production and epigastric bloating and a decreased incidence of ability to relieve bloating in patients who underwent division of the short gastric vessels. CONCLUSIONS: Division of the short gastric vessels during laparoscopic Nissen fundoplication does not improve any measured clinical outcome at 5 years of follow-up and is associated with an increased incidence of “wind-related” problems.